56 Examining Fall-Related HIP Fractures in Long-Term Residential Aged Care and the Community: Trends, Health Outcomes and Treatment Costs. (20th December 2019) - Mitchell, Rebecca; Draper, Brian; Harvey, Lara; Brodaty, Henry; Close, Jacqueline
Abstract: Background: Hip fracture risk is higher for older adults living in residential aged care facilities (RACF) and their health outcomes worse compared to older adults living in the community. Pre-hip fracture residential status is not well recorded within hospital records, necessitating linkage of hospital and residential aged care data to better ascertain residential location pre-fracture. Aim: To examine temporal trends, characteristics and health outcomes following a fall-related hip fracture hospitalisation of people living in RACFs to those living in the community. Method: A retrospective analysis of fall-related hip fracture hospitalisations of people aged ≥65 years during 2008-2013 in New South Wales, Australia. Linked hospitalisation and RACF data were examined. Negative binomial regression examined the significance of hospitalisation temporal trends. Results: There were 28, 897 hip fracture hospitalisations and 32.5% were living in RACFs at time of fracture. The hospitalisation rate was 2, 180 per 100, 000 (95%CI: 2, 097.0-2, 263.7) for RACF residents and 390 per 100, 000 (95%CI 384.8-395.8) for the community-living. Over 5 years, the hospitalisation rate for RACF residents declined by 2.9% annually (95%CI: -4.3 to -1.5). Hospital treatment cost for hip fractures was $958.5 million. Compared to older people living in the community, a higher proportion of RACF residents were aged ≥90 years (36.1% vs 17.2%), were female (75.3% vs 71.8%), had >1 Charlson comorbidity (37.6% vs 35.6%), and had dementia (58.2% vs 14.4%). RACF residents had fewer in-hospital rehabilitation episodes (18.7% vs 60.9%) and a higher proportion of unplanned readmissions (10.6% vs 9.1%) and in-hospital mortality (5.9% vs 3.3%) compared to older people living in the community. Conclusions: RACF residents are a vulnerable cohort of older people who experience worse health outcomes and survival post-hip fracture than older people living in the community. Whether access to individualised hip fracture rehabilitation for RACF residents could improve health outcomes should be examined.